Design and synthesis of anticancer 1-hydroxynaphthalene-2-carboxanilides with a p53 independent mechanism of action - Spaczyńska, Ewelina; Mrozek-Wilczkiewicz, Anna; Malarz, Katarzyna; Kos, Jiri; Gonec, Tomas; Oravec, Michal; Gawecki, Robert; Bak, Andrzej; Dohanosova, Jana; Kapustikova, Iva; Liptaj, Tibor; Jampilek, Josef; et al. (Scientific reports, 2019)
A series of 116 small-molecule 1-hydroxynaphthalene-2-carboxanilides was designed based on the fragment-based approach and was synthesized according to the microwave-assisted protocol. The biological activity of all of the compounds was tested on human colon carcinoma cell lines including a deleted TP53 tumor suppressor gene. The mechanism of activity was studied according to the p53 status in the cell. Several compounds revealed a good to excellent activity that was similar to or better than the standard anticancer drugs. Some of these appeared to be more active against the p53 null cells than their wild-type counterparts. Intercalating the properties of these compounds could be responsible for their mechanism of action.
Keywords: nádorový supresorový protein p53; Doxorubicin; Models, Molecular; apoptóza; DNA; HCT116 buňky; Cell Proliferation; Naphthols; Tumor Suppressor Protein p53; HCT116 Cells; naftoly; interkalátory; Antineoplastic Agents; Intercalating Agents; knihovny malých molekul; Small Molecule Libraries; doxorubicin; molekulární modely; protinádorové látky; Humans; racionální návrh léčiv; proliferace buněk; Drug Design; lidé; Apoptosis